A Global African Buffalo Optimization - Azrag, M. A. K.; Tuty Asmawaty, Abdul Kadir; Odili, Julius Beneoluchi; Essam, M. H. A. (Penerbit UMP, 2017)
In this paper, a modified version of the African Buffalo Optimization algorithm with emphasis on global search is proposed. Two different equations with the values of their upper and lower boundaries are selected to be tested. The experimental result illustrates the difference in performance between the modified and the original ABO algorithm toward the optimum solution. At the end of all experimental procedures, it was observed that the Global African Buffalo Optimization (GABO) converges very quickly towards the optimal solution with a few buffalos. However, the experimental result show that GABO convergence still needs improvement as it tends to have unpromising convergence towards the end of a large iteration. In any case, GABO is a promising optimization method.